Family violence, employment status, welfare benefits, and alcohol drinking in the United States: what is the relation?. Issue 3 (1st March 2001) - Rodriguez, E; Lasch, K E; Chandra, P; Lee, J
Abstract : OBJECTIVES: This study examined the contribution of employment status, welfare benefits, alcohol use, and other individual, and contextual factors to physical aggression during marital conflict. METHODS: Logistic regression models were used to analyse panel data collected in the National Survey of Families and Households in 1987 and 1992. A total of 4780 married or cohabiting persons re-interviewed in 1992 were included in the analysis. Domestic violence was defined as reporting that both partners were physically violent during arguments. RESULTS: It was found that non-employed respondents are not at greater risk of family violence in comparison with employed respondents, after controlling for alcohol misuse, income, education, age, and other factors; however, employed persons receiving welfare benefits are at significantly higher risk. Alcohol misuse, which remains a predictor of violence even after controlling for other factors, increases the risk of family violence while satisfaction with social support from family and friends decreases it. CONCLUSION: These results underscore the important effect of alcohol misuse on domestic violence, and the need to monitor the potential impact of welfare reform on domestic violence.